Come home to supper ebook Over 200 casseroles, skillets, and sides (desserts, too!)—to feed your family with love. - Jordan, Christy (2013)
It's a heartfelt celebration of family dinners—the comforting, delicious food that memories are made of—by the new doyenne of Southern cooking. Christy Jordan is a former editor-at-large of Southern Living , a contributing editor to Taste of the South , and publisher of the wildly popular blog SouthernPlate.com—boasting nearly 1 million unique visitors per month, over 60,000 e-newsletter subscribers, and more than 50,000 Facebook fans. She's appeared on TODAY , Paula Deen , and QVC, among many other media outlets, and her first book, Southern Plate (William Morrow), has 107,000 copies in print. Conceived and written to reflect the reality of today's hectic schedules—and the need to gather around the dinner table— Come Home to Supper offers more than 200 deeply satisfying dishes that are budget-minded, kid-friendly, and quick. These are the everyday meals that Christy Jordan most loves to cook, and her family most loves to eat, and she serves them up with generous helpings of her folksy wisdom, gratitude, and lively stories. Many of the recipes make ingenious use of the slow cooker or a single pot or skillet; require easily found supermarket ingredients; and are packed with time-saving tips and shortcuts. And the menu, well, it's all good, includingCrispy Breaded Pork Chops with Milk Gravy, Beef and Broccoli,Spicy Fried Chicken,Craving Beans, Summer Corn Salad, Slow Cooker Baked Apples,Ice Cream Rolls, andCinnamon Pudding Cobbler. Or to put it like Christy Jordan, food to make your family "smile louder."